(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2026)
This article analyzes the semantic and syntactic features of wordplay and metaphors in the Uzbek language. It explores the linguistic and cultural layers of wordplay, the logical-semiotic essence of metaphors, and their functional role in sentence structure. Based on examples from literary texts and public speech, the article reveals the interaction between semantic coherence and syntactic constructions.